Banking Mergers and Acquisitions in the EU: Overview, Assessment and Prospects - Rym Ayadi; Georges Pujals (SUERF - The European Money and Finance Forum, 2005)
This paper aims at providing a complete picture of banking mergers and acquisitions (M&As) in Europe during the 1990s and at offering economic evaluation and strategic analyses of the process. The main characteristics of this process in the 1990s were the emergence of " mega banks" at the national scale, a slight increase of cross-border transactions and the emergence of few large pan-European financial groups. Building on an extensive review of the US and EU literature, we examine the impact of M&As in European banking on profitability and efficiency, considering the breakdown between domestic and cross-border transactions. We first proceed with the profitability analysis of distinct completed M&As cases with different industrial strategies (based on the geographical dimension of the transaction and the initial activities of the merging banks). We find that domestic mergers contribute to cut costs for both partners, whereas, for the majority of cases studies, including domestic and cross-border mergers and acquisitions, the impact on profitability is insignificant, but a clear trend to diversify the sources of revenues was apparent. The cost and profit efficiency analysis based on 33 bank-to-bank mergers, confirmed an improvement of cost efficiency and little improvement of profit efficiency for domestic transactions; whereas, no improvement of costefficiency and a little improvement of profit efficiency for cross-border transactions. These results imply that domestic banking mergers in Europe fulfilled their objective to cut costs whereas they failed to achieve revenues synergies; cross-border mergers instead, were proved to better exploit from revenues synergies more likely due to geographical diversification. Against this background, we provide the main prospective scenarios for banking consolidation in the medium term after examining the state of concentration and competition in the domestic banking markets and the role of the regulatory changes and remaining obstacles to a full European banking integration. Finally, we raise the main strategic challenges ahead banking institutions in terms of business models - Universal, multi specialised or specialised banking, optimal size, growth strategies - M&As or partnerships - and the prospects offered by the new Basel capital Accord. A first appraisal suggests: a) a natural coexistence of different business models, each one having its specific characteristics and responding to individual needs, b) the optimal size is not synonym of a larger size and a larger size is not an absolute criterion of profitability and efficiency, c) M&As are not the only alternative to banking consolidation, and d) finally Basel II is redefining the rules of the game to European banking, but it is rather premature to make a final and exhaustive assessment in this respect.
Keywords: G21; G28; G34; 330; Banking mergers and acquisitions; profitability; efficiency; market power; concentration; competition; banking model; Universal banking; diversification; specialisation; Basel II; Übernahme; Bank; EU-Staaten